2002
DOI: 10.1038/nature01091
|View full text |Cite
|
Sign up to set email alerts
|

A satellite view of aerosols in the climate system

Abstract: Anthropogenic aerosols are intricately linked to the climate system and to the hydrologic cycle. The net effect of aerosols is to cool the climate system by reflecting sunlight. Depending on their composition, aerosols can also absorb sunlight in the atmosphere, further cooling the surface but warming the atmosphere in the process. These effects of aerosols on the temperature profile, along with the role of aerosols as cloud condensation nuclei, impact the hydrologic cycle, through changes in cloud cover, clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
1,276
2
24

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 2,053 publications
(1,331 citation statements)
references
References 93 publications
29
1,276
2
24
Order By: Relevance
“…Since then, we found that clouds and aerosols (natural or pollution particles suspended in the air) play a critical role in determining cloud cover, precipitation, evaporation, and the response of the climate system to anthropogenic emissions [Gunn and Phillips, 1957;Ramanathan et al, 2001;Kaufman et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, we found that clouds and aerosols (natural or pollution particles suspended in the air) play a critical role in determining cloud cover, precipitation, evaporation, and the response of the climate system to anthropogenic emissions [Gunn and Phillips, 1957;Ramanathan et al, 2001;Kaufman et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric particles have an influence on the global climate system, providing an adverse effect on human health and visibility (Huebert et al, 2003;Kaufman et al, 2002;Menon et al, 2002;Richter et al, 2005). Severe droughts in northern China and enhanced summer floods in southern China may be associated with the anthropogenic atmospheric particles that modify the regional air circulation (Menon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the air qualitymonitoring stations are located close to major urban areas leaving large areas without operational observations. Satellite remote sensing is well suited for a daily monitoring of the aerosol load (Kaufman et al, 2002;King et al, 1999). In the recent years several set of satellite data have fostered a comprehensive description of the temporal and spatial variability of different aerosol species, from anthropogenic aerosols ) to desert dust (Léon and Legrand, 2003).…”
Section: Introductionmentioning
confidence: 99%